Pengaruh Pelatihan, Pengembangan dan Kepuasan Karyawan Terhadap Kinerja Karyawan Di PT XYZ - Violeta Laurensia (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
Human resource is one of the most important aspects of an organization. There are several indicators that can influence human resources which include but not limited to training, development, performance, and satisfaction. The goal from this research is to analyze the effect of training on employees’ performance, to analyze the effect of development on employees’ performance, to analyze the effect of employees’ satisfaction on their performance, and to analyze the effect of training and development on employees’ performance in PT XYZ. The sample size in this study is 70 people. The method used in this study is quantitative and the instrument used is questionnaire which is then analyzed using SPSS 22. The results are: (1) Training have a significant influence on employees’ performance (p-value < 0.05, 0.004), (2) Development do not have a significant influence on employees’ performance (p value > 0.05, 0.473), (3) Employees’ satisfaction have a significant influence on employees’ performance (p-value < 0.05, 0.00), (4) Training and development have a significant influence on employees’ performance (sig. value < 0.05 in the Anova test, 0.00).